Town Planning in Hong Kong : A Review of Planning Appeals - Lai, Lawrence Wai-chung (Book collections on Project MUSE., 1999)
This book is written for professionals and practitioners who are interested in town planning, such as policymakers who deal with planning and development matters, lawyer, developers, proprietors, town planners, environmental protection officers and transport officers in the government and private practice, members of the Town Planning Board and Town Planning Appeal Board, estate and building surveyors, architects, authorized persons and academics whose research area is in planning and decision-making of statutory bodies, particularly those who are interested in "rent-seeking," "economic analysis of law" and "property rights." There has been in recent years rapid expansion and development in the Town Planning Ordinance, which was first passed in 1939, and the ensuing case law. However, there have been few systematic publications on statutory planning in Hong Kong from the perspective of law, planning or valuation. Law schools in Hong Kong have only just begun to develop a relevant curriculum, and lawyers and professionals specialized in planning law are in great demand. Such demand is generated by the fact that statutory planning has become increasingly litigious due to its successive amendments and the sustained rise in economic and environmental values of land. Planning and surveying schools have also been slow in integrating their specialisms in one curriculum. While planners tend to ignore the economic or valuation implications of their practice, educators in surveying do not seem to understand thoroughly the importance of town plans or planning constraints: they are key factors affecting land values.